4B.05: PLASMA COPEPTIN IS ASSOCIATED WITH INSULIN RESISTANCE IN A SWISS POPULATION-BASED STUDY. (June 2015) - Canivell, S.; Ponte, B.; Pruijm, M.; Ackermann, D.; Guessous, I.; Ehret, G.; Paccaud, F.; Pechere-Bertschi, A.; Mohaupt, M.; Vogt, B.; Burnier, M.; Devuyst, O.; et al.
Abstract : Objective: Previous studies suggest that arginine vasopressin may have a role in metabolic syndrome (MetS) and diabetes by altering liver glycogenolysis, insulin, and glucagon secretion and pituitary ACTH release. We tested whether plasma copeptin, the stable C-terminal fragment of arginine vasopressin prohormone, was associated with insulin resistance and MetS in a Swiss population-based study. Design and method: We analyzed data from the population-based Swiss Kidney Project on Genes in Hypertension. Copeptin was assessed by an immunoluminometric assay. Insulin resistance was derived from the HOMA model and calculated as follows: (FPI x FPG)/22.5, where FPI is fasting plasma insulin concentration (mU/L) and FPG fasting plasma glucose (mmol/L). Subjects were classified as having the MetS according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Mixed multivariate linear regression models were built to explore the association of insulin resistance with copeptin. In addition, multivariate logistic regression models were built to explore the association between MetS and copeptin. In the two analyses, adjustment was done for age, gender, center, tobacco and alcohol consumption, socioeconomic status, physical activity, intake of fruits and vegetables and 24 h urine flow rate. Copeptin was log-transformed for the analyses. Results: Among the 1, 089 subjects included in this analysis, 47% were male. Mean (SD) age and body mass index were 47.4 (17.6) years 25.0 (4.5) kg/m2. The prevalence of MetS was 10.5%. HOMA-IR was higher in men (median 1.3, IQR 0.7–2.1) than in women (median 1.0, IQR 0.5–1.6, P < 0.0001). Plasma copeptin was higher in men (median 5.2, IQR 3.7–7.8 pmol/L) than in women (median 3.0, IQR 2.2–4.3 pmol/L), P < 0.0001. HOMA-IR was positively associated with log-copeptin after full adjustment (β (95% CI) 0.19 (0.09–0.29), P < 0.001). MetS was not associated with copeptin after full adjustment (P = 0.92). Conclusions: Insulin resistance, but not MetS, was associated with higher copeptin levels. Further studies should examine whether modifying pharmacologically the arginine vasopressin system might improve insulin resistance, thereby providing insight into the causal nature of this association.